Weed management module for Indian mustard (Brassica juncea L.) (Journal of Oilseed Brassica, 2026)
A field experiment was conducted at Govind Ballabh Pant University of Agriculture & Technology, Pantnagar during rabi season of 2019-20 for exploration of weed management module for Indian mustard (Brassica juncea L.). The thirteen treatment combinations of different weedicides and their application rates along with weedy check (control) were accommodated in randomized complete block design with three replications. The maximum values of yield attributing characters i.e. number of branches per plant, number of siliquae/plant, seed weight per plant seed yield was obtained with application of pendimethalin @ 1.0 kg a.i./ha (PE) + hand weeding (HW) at 30 days after sowing (DAS). Pendimethalin @ 1.0 kg a.i./ha (PE) + HW) at 30 DAS also recorded the maximum weed control efficiency, seed yield and B:C ratio over the other treatments.